2014
DOI: 10.1103/physrevb.90.165306
|View full text |Cite
|
Sign up to set email alerts
|

Geometric and compositional influences on spin-orbit induced circulating currents in nanostructures

Abstract: Circulating orbital currents, originating from the spin-orbit interaction, are calculated for semiconductor nanostructures in the shape of spheres, disks, spherical shells, and rings for the electron ground state with spin oriented along a symmetry axis. The currents and resulting orbital and spin magnetic moments, which combine to yield the effective electron g factor, are calculated using a recently introduced formalism that allows the relative contributions of different regions of the nanostructure to be id… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 45 publications
1
12
1
Order By: Relevance
“…We note that this relation can be derived using the Zeeman interaction and time-reversal symmetry; the factor 2 arises from Kramer's degeneracy. It has been shown [20] that μ z spin is nearly always equal to μ B . In Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We note that this relation can be derived using the Zeeman interaction and time-reversal symmetry; the factor 2 arises from Kramer's degeneracy. It has been shown [20] that μ z spin is nearly always equal to μ B . In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This dependence is therefore related to the size dependence of the integrated current [20]. For the small heights considered here, the integrated current gets smaller with decreasing height: the valence-band contributions to the electron ground state are quenched through their dependence on the confinement energy.…”
Section: B Electron G Factorsmentioning
confidence: 86%
See 1 more Smart Citation
“…The g tensor depends on the exact electronic structure of the QD and therefore also has a strong dependency on the size and shape of quantum dots [6][7][8]. This implies that the g tensor in a QD can be manipulated in situ by changing its electronic structure, for instance by means of an externally applied electrical or elastic stress field.…”
mentioning
confidence: 99%
“…Previous work on InAs QDMs has shown that the Zeeman splitting between spin projections can be a function of applied vertical electric field due to the changing spatial distribution of electron or hole wavefunctions. 13,15,[39][40][41][42] In our case, the changing Zeeman splitting originates, at least in part, from the changing spatial extent of the hole wavefunctions induced by the applied lateral electric field. This dependence of the hole wavefunction distribution on lateral field is displayed in Figure 2c.…”
Section: A Symmetric Qdm Without Piezoelectric Fieldmentioning
confidence: 99%